Rufus Hallmark, Frauenliebe und Leben: Chamisso’s Poems and Schumann’s Songs (2014) - Kenny, Aisling (Journal of the Society for Musicology in Ireland, 2018)
A review of Rufus Hallmark, Frauenliebe und Leben: Chamisso’s Poems and Schumann’s Songs (Cambridge University Press, 2014), ISBN 978-1-00230-2.